Metallic MXene Saturable Absorber for Femtosecond Mode-Locked Lasers - Jhon, Young In; Koo, Joonhoi; Anasori, Babak; Seo, Minah; Lee, Ju Han; Gogotsi, Yury; Jhon, Young Min (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2017)
2D transition metal carbides, nitrides, and carbonitides called MXenes have attracted much attention due to their outstanding properties. However, MXene's potential in laser technology is not explored. It is demonstrated here that Ti3CN, one of MXene compounds, can serve as an excellent mode-locker that can produce femtosecond laser pulses from fiber cavities. Stable laser pulses with a duration as short as 660 fs are readily obtained at a repetition rate of 15.4 MHz and a wavelength of 1557 nm. Density functional theory calculations show that Ti3CN is metallic, in contrast to other 2D saturable absorber materials reported so far to be operative for mode-locking. 2D structural and electronic characteristics are well conserved in their stacked form, possibly due to the unique interlayer coupling formed by MXene surface termination groups. Noticeably, the calculations suggest a promise of MXenes in broadband saturable absorber applications due to metallic characteristics, which agrees well with the experiments of passively Q-switched lasers using Ti3CN at wavelengths of 1558 and 1875 nm. This study provides a valuable strategy and intuition for the development of nanomaterial-based saturable absorbers opening new avenues toward advanced photonic devices based on MXenes.